Sward structure and ingestive behavior of cows in tropical pastures managed under different forage allowances - Janusckiewicz, E. R.; Casagrande, D. R.; Raposo, E.; Bremm, C.; Reis, R. A. [UNESP]; Ruggieri, A. C. [UNESP] (Arquivo Brasileiro Medicina Veterinaria Zootecnia, 2019)
This study evaluated how changing the structure of Brachiaria brizantha cv. Marandu pasture under different forage allowances (FA) of 4, 7, 10 and 13kg DM/100kg BW (body weight) affected animal behavior over a two-year evaluation period. The experiment was conducted as a randomized block design with three replications (paddock). Sward height, total forage, and stem mass were lower for pastures managed with lower FA. Lower leaf mass was observed for lower FA in the second year. In hand-plucked samples, leaf and stem percentages remained unchanged in the morning but leaf percentage increased while stems decreased in the afternoon. Permanence time decreased linearly with increasing FA. In turn, a quadratic effect was observed for displacement rate. The bite rate was similar among different FAs. The results demonstrate that FA varying between 7 and 10kg DM/100kg BW are more suitable to balance the amounts of leaves and stems in the sward. The studied FA levels do not limit forage availability. Permanence time decreases and displacement rate increases as FA increases.
Keywords: bite rate; displacement; forage mass; sward height